Human chorionic gonadotropin and Testosterone in Normal and Preeclamptic Pregnancies in Relation to Fetal sex - Al-Adami, Maad S.; Wajdi, Wasan; Abbas, Rawneq A. (AL-Kindy College Medical Journal, 2011)
Back ground: The gender related difference may be the result of pregandiol excretion in the latter half of pregnancy. Aim: This study is to evaluate the effects of fetal gender on serum human chorionic gonadotropin [HCG] and testosterone in normotensive and preeclamptic pregnancies Methods: The study consisted of fifty women with singleton pergnancy in their third trimester. Twenty five pregnancies were uncomplicated Among those there were thirteen male, and twelve female fetuses Twenty five pregnancies were complicated by preeclampsia. Among those thirteen were with male, and twelve were with female fetuses. Human chorionic gonadotropin and total testosterone were measured in maternal peripheral blood. Results: In male bearing pregnancies, maternal HCG and testosterone serum levels were significantly higher in preeclamptic than in normotensive mothers. In female bearing pregnancies, testosterone levels were significantly higher in preeclamptic than normotensive mothers, whereas the HCG levels were not significantly different.Male Bearing preeclamptic women had significantly higher testosterone levels than female Bearing preeclamptic women, whereas the HCG levels were not significantly different. In uncomplucated pregnancies the HCG levels significantly higher in female bearing than in male bearing mothers, Conclusion: In preeclamptic pregnancies with male fetuses; the maternal serum HCG levels were significantly higher than in uncomplicated pregnancies. Total testosterone level were significantly higher in pregnancies whether with male or female fetuses. It was also significantly higher in male bearing than female bearing pregnancies. This may indicate an androgen influence on the pathophysiologic of preeclampsia